Unjuk Kerja Reflektor Radiasi Panas dengan 1 Baris Sirip terhadap Efisiensi Kompor LPG - Sudarno, Sudarno; Soeparman, Sudjito; Wahyudi, Slamet; Widodo, Agung Sugeng (Jurnal Rekayasa Mesin, 2018)
It has been known from the previous researchers that the use of the heat radiation reflector can improve the efficiency of the LPG stoves. Based on the radiation theory, the radiation energy is emitted radially in all directions. Therefore, a kind of method to guide the heat radiation is required to minimize the heat losses. One of the method is to add some fins to the reflector in order to capture the potential heat loss from the non-finned reflector. In this work, we use one fin line reflector made from a plate of stainless steel in the shape of cutted-cone. The boiling water test is used to investigate the efficiency of LPG stoves. We find that the efficiency of LPG stoves can be increased by adding one fin line reflector by about 5.21% and 1.75% than that one without reflector and non-finned reflector, respectively. The result of the temperature distribution shows that one fin line reflector enlarges the area of complete combustion.